(untitled) (Research, Society and Development, 2020)
This research has as main objective to study the practices of the program MasterChef BR da Rede Bandeirantes in the attempt to establish interactivity with the user / viewer. As secondary objectives, it was defined: to classify the type of interaction used in the third season of the program MasterChef Brazil professionals; identify the level of interactivity used in the program; Classify the interaction possibilities that are offered in MasterChef BR from the integration of the first screen with the digital platform Twitter; and compare the possibilities of interactivity between the program and Twitter. For that, a qualitative, exploratory and descriptive research was used as a methodology for this work, based on content analysis and indirect observation techniques, for the purpose of understand the data obtained during the transmissions of the programs from August 21 to December 11, 2018. In the analyzes, it was found that although the MasterChef is interactive and seeks to encourage the participation of its viewers, the actions of the public are predetermined from the possibilities that are offered by the production of the program.